"Smart Tuning" As a Discourse Technology of Effective Communication - I.A. Yakoba (Дискурс Пи, 2017)
Statement a problem of discourse technologization is one of relevant topics of a race for power and communication management for social control. This paper researches the discourse from position of technological effectiveness of addresser and addressee interaction, discourse power parameterization that defines discourse action quality. "Smart tuning" technology reveals smart power potential that is used for effective communication in a technological discourse.